On the pathogenetic classification of primary angleclosure glaucoma - N. A. Bakunina; L. M. Balashova (Российский офтальмологический журнал)
Purpose: to clarify the pathogenetic classification of primary angle-closure glaucoma (PACG) based on genetic studies and retrospective analysis.Material and methods. 28 patients (44 eyes) aged 40 to 75 years with various forms of initial, advanced, advanced and terminal stages of PACG, as well as combined glaucoma, were observed.Results. Pathogenetically significant genetic polymorphisms responsible for synechiogenesis in chronic PACG have been found. Clinical and genetic analysis of PACG showed that the classification based on the clinical course, the mechanisms of closure of the iridocorneal angle (ICA), the distribution by stages of primary closure of the ICA, the severity of the pathological process and the level of intraocular pressure, fail to take into account the genetic characteristics of patients with PACG: these are predetermined at birth. In appositional closure of the ICA, preventive laser iridotomy is indicated, while in synechial closure, preventive iridotomy may aggravate synechiogenesis.Conclusion. A pathogenetic classification of PACG has been proposed, which takes account of its hereditary nature. This classification, is advisable to use when choosing a treatment tactics.